Presidential Versus Parliamentary Systems: Where Do Female Entrepreneurs Thrive?. (8th August 2020) - Goel, Rajeev K.; Nelson, Michael A.
Abstract : Objective: This article examines whether female managers and female owners of firms are better empowered in presidential or parliamentary democracies. Parliamentary democracies might be more responsive to the demands of special interest groups, while government decision making might be more streamlined in presidential democracies. Methods: We use firm‐level data from the World Bank for more than 100 emerging and developing nations and employ the logistic estimation procedure. Results: Results show that female owners of firms thrive in presidential democracies, but the effects on female managers were largely statistically insignificant. Other interesting findings include both female managers and female owners facing special challenges in nations with greater gender inequality, with female owners benefiting in nations with a larger informal sector. Conclusions: Our results show that the type of democracy is relevant in female entrepreneurship, with female owners of firms thriving in presidential democracies, but not necessarily female managers.